Dogs Health Care Management System - Balasooriya B.M.D.D; Rathnayaka R.M.S.Y; Dilshani M.G.S.U; Perera K.S.C; D. I. De Silva; H.M.P.K. Samarasekara (International Journal of Engineering and Management Research, 2022)
Web based applications have become an important part of daily life as it improves inefficient resources management while saving time. With the advancement of technology, every business sector tries to introduce software systems with smart features Life has become too busy to schedule and keep up with pets' necessary medical appointments and care. There are currently a smaller number of online applications for veterinary systems. So, this study designs an online system to fill up that research gap. In this project, a JavaScript based application is designed with features such as booking an appointment by checking a doctor's availability and all those details are going to store in a database. This also records all the details of the dogs that come to the hospital for daily treatments. With the help of daily clinical data, veterinary health care owners can easily identify active clients and give offers easily. Moreover, newly introduced features are caused to increase the efficiency and maintenance of the system. However, this application addresses not only the pet lovers’ difficulties regarding the veterinary health, but it also addresses management side problems as well. This system is designed and implemented not only for the pets, but also considering orphan dogs. So, this system provides volunteer service as well.